Answer:
c) x = 11
Step-by-step explanation:
Given equation: 7x - 9 = 28 + 4(x - 1)
<u><em>Steps:</em></u>
1. Distribute 4 through the parentheses:
7x - 9 = 28 + 4(x) + 4(-1)
7x - 9 = 28 + 4x - 4 [simplify]
7x - 9 = 24 + 4x
2. Subtract 4x from both sides:
7x - 4x - 9 = 24 + 4x - 4x
3x - 9 = 24
3. Add 9 to both sides:
3x - 9 + 9 = 24 + 9
3x = 33
4. Divide both sides by 3:
3x ÷ 3 = 33 ÷ 3
x = 11
5. Check your work:
7x - 9 = 28 + 4(x - 1) [substitute 11 for x]
7(11) - 9 = 28 + 4(11 - 1) [simplify]
77 - 9 = 28 + 4(10) [simplify]
68 = 28 + 40 [add]
68 = 68 ✔
Learn more here:
brainly.com/question/27844321
brainly.com/question/21222758
Thus is how you write y=2x-7 in a function notation. ANSWER:F(x)=2x-7.
Answer: The number is 15
Step-by-step explanation: basically the equation you should solve is
(x)+(2x)+(2x+7)=82
5x+7=82
5x= -7+82
5x=75
5/5x=75/5
x=15
Answer:
y= -3/5x+5
Step-by-step explanation:
Answer:
3/4 - 5/12
Step-by-step explanation:
first you make the demoninators the same so 3*4=12
and if you *3 you do it to the numerator
so its 9/12-5/12
the unsimplified fraction is 4/12
if wanted simplified version its 1/3